“...JUNTOS Y A SON DE CAMPANA CONGREGADOS”: ELITE’S PRESTIGE AND SOCIABILITY IN SANTIAGO’S BROTHERHOODS (1700-1770) - Ovalle Letelier, Alex (Revista de Historia Social y de las Mentalidades, 2024)
This article analyzes the social practices regarding three “cofradías” in Santiago, which received the city elite between 1700 an 1770 and having as a starting point the influences underlying the institutional structure, which were represented in the political field and in the brotherhood administration. The “cofradías” are regarded as social instances which made social prestige, possible and worth demonstrating. Its administration and charity are part of the distinguishing strategies which the elites in Santiago would adopt during the firs half of the XVIII century